Machine learning and data mining : methods and applications (Chichester, England : John Wiley and Sons, 1998)
General topics. Design and engineering. Detection of patterns in texts, images and music. Computer systems and control systems. Medicine and biology.
Keywords: Computer; Machine learning; Data mining; Machine learning; Data mining